Src Family Kinases Play a Role in the Functional Clustering of Central Postsynaptic Nicotinic Acetylcholine Receptors - Flynn, Nichole; Syed, Naweed I. (Frontiers in Marine Science, 2020)
The mechanism of postsynaptic neurotransmitter receptor clustering has been best described at the neuromuscular junction (NMJ), where packets of nicotinic acetylcholine receptors (nAChRs) in muscle fibre are redistributed to the synaptic site upon motor neuron innervation. This process of receptor localisation is facilitated by agrin signalling, and the stability of the resulting nAChR clusters depends upon the activation of Src family kinases (SFKs). In contrast to the NMJ however, the cellular signalling mechanisms orchestrating the clustering of nAChRs in the central nervous system (CNS) remain poorly defined. Furthermore, our understanding of the role of SFKs in the CNS is also limited. Here we provide evidence that SFK activation is required for synapse formation between pairs of identified neurons isolated from the CNS of Lymnaea stagnalis. Furthermore, we suggest that SFKs are involved in the functional redistribution of nAChRs to the synaptic contact sites in isolated axons. To the best of our knowledge, this study is the first to demonstrate a role for SFKs in the clustering of nAChRs in central neurons, suggesting that the mechanisms of receptor clustering between the peripheral and central nervous system are likely conserved.